2002
DOI: 10.4049/jimmunol.169.8.4572
|View full text |Cite
|
Sign up to set email alerts
|

House Dust Mite Allergens Induce Proinflammatory Cytokines from Respiratory Epithelial Cells: The Cysteine Protease Allergen, Der p 1, Activates Protease-Activated Receptor (PAR)-2 and Inactivates PAR-1

Abstract: In previous studies, we demonstrated that allergenic house dust mite proteases are potent inducers of proinflammatory cytokines from the respiratory epithelium, although the precise mechanisms involved were unclear. In this study, we investigated whether this was achieved through activation of protease-activated receptor (PAR)-1 or -2. Pretreatment of A549 respiratory epithelial cells with the clinically important cysteine protease allergen, Der p 1, ablated subsequent PAR-1, but not PAR-2 agonist peptide-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
247
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 323 publications
(256 citation statements)
references
References 45 publications
6
247
3
Order By: Relevance
“…Although the precise role of Pen c 13 in allergic disease is unclear, fungal proteases have been linked to allergic asthma, and many of the Ags frequently implicated in disease are proteases. In previous studies, the house dust mite allergens, Der p 1, Der p 3, and Der p 9, were found to activate PAR-2 and stimulate the release of the proinflammatory cytokines, GM-CSF, eotaxin, IL-6, and IL-8, by human lung epithelial cells (2,3). Cockroach extract also increases IL-8 expression in human bronchial epithelial cells via PAR-2 activation (4 -6).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the precise role of Pen c 13 in allergic disease is unclear, fungal proteases have been linked to allergic asthma, and many of the Ags frequently implicated in disease are proteases. In previous studies, the house dust mite allergens, Der p 1, Der p 3, and Der p 9, were found to activate PAR-2 and stimulate the release of the proinflammatory cytokines, GM-CSF, eotaxin, IL-6, and IL-8, by human lung epithelial cells (2,3). Cockroach extract also increases IL-8 expression in human bronchial epithelial cells via PAR-2 activation (4 -6).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, an extract of German cockroach (Blattella germanica) contains proteolytic activity that causes an increase in TNF-␣-induced IL-8 expression in human bronchial epithelial cells (4). The effects of these aeroallergen proteases, acting via protease-activated receptors (PARs), 3 have been implicated in the regulation of the release of proinflammatory cytokines, such as eotaxin, GM-CSF, IL-6, and IL-8, by epithelial cells in a nonallergic inflammatory response (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). PARs appear to play a proinflammatory role by activating proinflammatory cytokines (11,12).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The best studied protagonist is PAR-2, as this receptor has been associated with activation by allergens. Activation of PAR-2 by proteases is associated with house dust mite allergen (82), cockroach allergen (83), trypsin (84) or PAR-2 activating peptides (74) and has been reported for many different epithelial cell lines or primary cells (81,85). The extend of these responses nor their similarity is not fully clear, as in many studies only a limited set of outcome parameters (mostly IL-6 and IL-8) are reported.…”
Section: Epithelial Expression Of Parsmentioning
confidence: 99%
“…Further studies in HEK293 cells exposed to Candida supernatant or SAP2 revealed that neither stimuli affected par mRNA expression. With Aspergillu s, despite the ability to inhibit trypsin signaling, culture supernatant did not affect either PAR expression while, similar to other protease allergens, 26 Aspf18 downregulated the expression of par1 ( Supplementary Figure S1 online). Thus, Candida activates PAR 1 and PAR 2 by a TLR2-dependent mechanism, an effect that is not mediated by fungal proteases, while Aspergillus proteases may contribute to the downregulation of trypsin-induced activation of PAR 2 , which occurs by a TLR4-dependent mechanism.…”
Section: Fungal Proteases Contribute To Par Activationmentioning
confidence: 99%